Creating Transient Gradients in Supramolecular Hydrogels. Issue 10 (16th April 2020) - Thomson, Lisa; Schweins, Ralf; Draper, Emily R.; Adams, Dave J.
Abstract: The self‐assembly of low molecular weight gelators in water usually produces homogeneous hydrogels. However, homogeneous gels are not always desired. Using a photoacid generator, it is shown how to form gels with a transient gradient in stiffness, proved using cavitation and bulk rheology. Small‐angle neutron scattering is used to show that the gels formed by photoacid are the result of the same structures as when using a conventional pH trigger. Patterned gels can also be formed, again with transient differences in stiffness. Abstract : Gels with transient gradients in stiffness can be created using a photoacid. By combining a conventional acid and a photoacid and a single gelator, it is shown that stiffness and gradients can be finely controlled.